2021
DOI: 10.1186/s12974-020-02070-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammatory processes are augmented in mice overexpressing human heat-shock protein B1 following ethanol-induced brain injury

Abstract: Background Heat-shock protein B1 (HSPB1) is among the most well-known and versatile member of the evolutionarily conserved family of small heat-shock proteins. It has been implicated to serve a neuroprotective role against various neurological disorders via its modulatory activity on inflammation, yet its exact role in neuroinflammation is poorly understood. In order to shed light on the exact mechanism of inflammation modulation by HSPB1, we investigated the effect of HSPB1 on neuroinflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 97 publications
1
12
0
Order By: Relevance
“…A heat map indicating relative expression of the downstream target molecules identified in our proteomic analysis for all three regions is depicted in Figure 3b. Many of the mapped strongly elevated proteins common to the hippocampus and thalamus are specifically expressed in astrocytes, including Hspb1, S100a6, Clu, Htra1, and GFAP (Dukay et al, 2021;Launay et al, 2008;Morgan et al, 1995;Nafar et al, 2016;Yamashita et al, 1999), while other markers such as Vim and ApoE can be expressed in both astrocytes and microglia (Graeber et al, 1988;O'Leary et al, 2020). Activation of TGF-β1 is consistent with our recent findings that its mRNA expression is significantly elevated in 12 M rTg-DI rats (Zhu, Hatfield, et al, 2020).…”
Section: Ipa Reveals Distinct Upstream Regulators and Casual Networksupporting
confidence: 89%
“…A heat map indicating relative expression of the downstream target molecules identified in our proteomic analysis for all three regions is depicted in Figure 3b. Many of the mapped strongly elevated proteins common to the hippocampus and thalamus are specifically expressed in astrocytes, including Hspb1, S100a6, Clu, Htra1, and GFAP (Dukay et al, 2021;Launay et al, 2008;Morgan et al, 1995;Nafar et al, 2016;Yamashita et al, 1999), while other markers such as Vim and ApoE can be expressed in both astrocytes and microglia (Graeber et al, 1988;O'Leary et al, 2020). Activation of TGF-β1 is consistent with our recent findings that its mRNA expression is significantly elevated in 12 M rTg-DI rats (Zhu, Hatfield, et al, 2020).…”
Section: Ipa Reveals Distinct Upstream Regulators and Casual Networksupporting
confidence: 89%
“…Previous studies have shown that sHsps are anti-inflammatory proteins. Overexpression of HspB1 ameliorates neuroinflammation caused by ethanol-induced brain injury in mice ( Dukay et al, 2021 ). HspB5 reduces inflammation by decreasing the secretion of proinflammatory cytokines in animal models of multiple sclerosis, ischemia, or nerve crush injury ( Kurnellas et al, 2012 ; Rothbard et al, 2012 ; Lim et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…As_9, over-represented in the E3 LPS brain, exhibited hallmark genes associated with scar formation and wound healing ( Cspg5, Htra1 ), 25,26 , while E4 LPS-enriched As_8/11 subtypes clustered similarly together and expressed genes associated with pro-inflammatory response ( Lcn2, Cxcl10 ), as well as oxidative stress and metal cation buffering (Fig. 1d; Hsbp1, S100a6, Mt1, Mt2 ) 2729 . Using Monocle2 as an alternate analysis pipeline, we demonstrate via pseudotime trajectory that several of the hallmark genes from As_8/11 are highly expressed in the E4_LPS condition (Fig 1e; purple).…”
Section: Resultsmentioning
confidence: 98%